Draft Annual Plan 2011-12 Volume-II (Tables) Government of Rajasthan - Planning Commission (Planning Commission, 2011)
Draft Annual Plan 2011-12 Proposed Outlay - Summary Draft Annual Plan 2011-12 Proposed Outlay (from State Budget) Draft Annual Plan 2011-12 Proposed Outlay (From Public Sector Enterprises) Draft Annual Plan 2011-12 Proposed Outlay (From Local Bodies) Draft Annual Plan 2011-12 Proposed Outlay - Scheme wise Draft Annual Plan 2011-12 Physical Targets and Achievements Draft Annual Plan - 2011-12 Statement Regarding Externally Aided Projects Draft Annual Plan - 2011- 12 Centrally Sponsored Schemes Draft Annual Plan 2011-12 - Financial Outlays : Proposals for TSP Scheduled Caste Sub-Plan (SCSP-I) Draft Annual Plan 2011-12 - Financial Outlays : Proposals for SCSP.
Government of Rajasthan, Planning Department